Pendekatan Tekstual dalam memahami Ayat-ayat Al-Qur’an tentang Prinsip Manajemen - As-Shidqi, Muhammad Haikal; Citra Atmaja, Abdul Haris (Jurnal Ilmu Pendidikan, 2024)
The management theories and concepts currently used are not something new from an Islamic perspective. Management has existed, at the very least, since Allah created the universe and everything in it. The elements of management in the creation of the universe and other creatures are closely intertwined with the management of the heavens. When Prophet Adam, as the caliph, led the cosmic order, he implemented these management elements. The Quran is believed to contain fundamental principles that pertain to all aspects of human life. Interpretation of the Quran needs to be an ongoing process. This is important because, on one hand, revelation and prophethood have concluded, while on the other hand, the conditions of the times continually change in line with human thought development, and there is still an absolute need for correct guidance for humanity.This article will discuss and analyze the Quranic verses related to management principles. The method to be employed is a descriptive analysis method that involves cataloging verses related to management principles and subsequently conducting textual analysis. This approach will allow for a careful examination of the Quranic text to extract the values and principles contained within it. Undoubtedly, these principles can provide a strong ethical guide for modern and complex management practices.